An Analysis of Students’ Anxiety in Speaking at Prabumulih University - Samosir, Hepnyi (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
The study is aimed at finding out the anxiety levels and possible factors that provoke the students’ anxiety. The study was conducted on 55 Information System students of Prabumulih University. To gain the data needed, a set of questionnaires consisting of 33 items was distributed to the students. The questionnaires were referred to the Foreign Language Classroom Anxiety Scale (FLCAS) designed by Horwitz et al. (1986). It aims to predict learners’ foreign language anxiety in the classroom in three domains: (1) communication apprehension; (2) test anxiety; and (3) fear of negative evaluation. Results show that (1) the students generally experienced a mildly anxious level with a mean of 90; (2), worry about failing exams, worry about making mistakes, low self-esteem, and less preparation are the factors that provoke the anxiety. The results reveal that the students’ anxiety is at a level that can be managed easily but if left unaddressed, it can lead to a higher level. Lecturers are expected to help students manage the students’ anxiety by paying attention to the factors that contribute to their anxiety.